Associação entre o polimorfismo VAL 158 MET da Catecol-o-metiltransferase (COMT) e aprendizagem motora - Nathálya Gardênia de Holanda Marinho Nogueira (2018)
Studies on cognitive functions and motor behavior show the Val and Met homozygotes of the catechol-o-methyltransferase (COMT) Val158Met polymorphism are associated with different levels of learning. In addition, there are indications of the effects of the COMT genotypes on the tonic and phasic roles of dopamine. However, studies that relate the COMT polymorphism and motor behavior did not investigate such association when using a motor sequence task that requires through learning the gain of stability and flexibility, fundamental characteristics of skilled behavior. Another important point is to investigate the association between the COMT polymorphism and the cortico-cortical communication. The present study aimed to investigate the association between the COMT Val158Met polymorphism and motor learning. A total of 42 university students of both sexes, right-handed, naïve on the task and with an average age of 25.1 ± 5.8 years participated in the study. The motor task consisted in pressing a sequence of keys on a numeric keypad with predetermined absolute and relative times. Three experimental groups were formed: Val/Val, Val/Met and Met/Met. Participants performed 120 trials of the motor task at three different total times: 700, 900 and 1,100 ms, and relative times that remained the same in all trials and had their cortical electrical activity recorded throughout the acquisition phase and on the learning tests by an electroencephalography device. The motor performance was evaluated by the relative and absolute errors and the cortico-cortical communication by the measure of coherence. One-way, two-way and three-way ANOVAs, linear regression and Pearson's correlation test were conducted in the statistical analysis. The results show that a better learning of the absolute time of the skill was observed in the homozygous Val subjects in the acquisition phase and in the learning test 1. However, unlike expected, homozygous Met subjects did not present a better learning level in the relative time. In addition, the results regarding the coherence showed that there were differences between groups in the acquisition phase and on the learning tests for the bands of interest.